Experimental investigations of CO2 absorption and catalyst-aided CO2 desorption performance of several different amines blending with a promoter. (31st December 2022) - Li, Tianci; Yang, Congning; Tantikhajorngosol, Puttipong; Sema, Teerawat; Tontiwachwuthikul, Paitoon
Graphical abstract: The reaction mechanism of the absorption and the catalytic desorption process. Highlights: Batch experiments were conducted in terms of initial absorption rate, initial CO2 desorption rate (non-catalytic, catalytic), and equilibrium CO2 solubility. Comprehensive comparison study of promoting efficiency using MEA and PZ into different single amines. Comparison of non-catalytic and catalytic desorption performance with the promoter at different conditions. Abstract: This research presented the new experimental results of the absorption and desorption performance of various single and blended solvents in terms of initial CO2 absorption rate, initial desorption rate for blank solvents and solvents with the aid of HZSM-5 catalyst, and equilibrium CO2 solubility. MEA and PZ are two promoters used to facilitate several individual aqueous single solvents including BEA, AMP, BDEA, and MDEA. In order to check the altered performance of absorption and desorption, the solvents were specified at 2.5 M. The initial desorption rate was evaluated by varying the temperature, weight of the solid catalyst, and initial rich CO2 loading. The experimental results were then taken to compare with the obtained data of the benchmark solution (2.5 M MEA). The comparison results revealed that all the selected blank solvent blends can provide better absorption and desorption performance than the blank benchmark solution. The results also indicated that the performance of catalyst-aided CO2 desorption could be strongly affected by the rich loading and operating temperature. Meaning that the activation of proton donation by HZSM-5 was patently affected by the above two conditions, which eventually affect the CO2 separation from the rich solvent.